1996
DOI: 10.1007/bf00395505
|View full text |Cite
|
Sign up to set email alerts
|

Spinal injuries in the pediatric age group: a review of 82 cases of spinal cord and vertebral column injuries

Abstract: A review of 82 children with spinal cord and/or vertebral column injury treated in our department between 1968 and 1993 showed that 67% of the patients were boys and the average age was 11.4 years. The cause, vertebral level, and type of injury, and the severity of neurological injury varied with the age of the patient. The cause of pediatric injuries differed from that of adult injuries in that falls were the most common causative factor (56%) followed by vehicular accidents (23%). The most frequent level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 29 publications
1
23
0
2
Order By: Relevance
“…The location of injury in patients with SCIWORA commonly involves the cervical cord, 20,21 but may also occur in the thoracic spine in association with high-energy trauma, 22,23 such as MVCs. Trigylidas and colleagues 20 found that 10% of myelopathic patients presented with associated head injuries and that 50% of these head injuries occurred in patients with SCIWORA.…”
Section: Discussionmentioning
confidence: 99%
“…The location of injury in patients with SCIWORA commonly involves the cervical cord, 20,21 but may also occur in the thoracic spine in association with high-energy trauma, 22,23 such as MVCs. Trigylidas and colleagues 20 found that 10% of myelopathic patients presented with associated head injuries and that 50% of these head injuries occurred in patients with SCIWORA.…”
Section: Discussionmentioning
confidence: 99%
“…The patient, however, was still treated with steroids, which is the treatment for an acute attack of chronic inflammation, for example, multiple sclerosis 15 or for SCIWORA. [3][4][5][6][7][8][9]16 Technically inadequate radiographic series of the cervical spine may miss the diagnosis of a cervical spine injury. Views required include a posterioanterior, lateral and odontoid view.…”
Section: Discussionmentioning
confidence: 99%
“…Turgut 7 described its incidence in 13% of the 82 children he treated with spinal cord and/or vertebral column injury. Pang, 2 on the other hand, reported its incidence at 66.7%.…”
Section: Introductionmentioning
confidence: 99%
“…Because one has access to the referring physician and clinical his toI)@ one could also develop a set ofclinical crite na that is most likely to identify a study with abnormal findings. AlthOUghsuch criteria have been developed for certain clinical presentations [18][19][20][21], suchcriteria haverarely beentestedor validated thmugh imaging studies. Our search method also allows the radiologist interpreting the study to track reports.…”
Section: Discussionmentioning
confidence: 99%